Quasinormal modes and greybody factors of f(R) gravity minimally coupled to a cloud of strings in 2+1 dimensions - Övgün, Ali; Jusufi, Kimet (Academic Press Inc Elsevier Science, 2018)
In this paper we have studied the propagation of a massless scalar field minimally coupled to a black hole with the source of cloud of strings in 2 + 1 f(R) gravity theory. In particular we have found analytical results for the decay rate, reflection coefficient, greybody factors, as well as the black hole temperature. On the other hand, our quasinormal modes analyses reveal stability in the propagation of a massless scalar field in the cloud of strings black hole spacetime. However, under a suitable choose of parameters an instability is found. Furthermore based on the Bekenstein conjecture on the quantization of the surface area of the black hole we find the minimal surface area associated to the black hole horizon which is in agreement with Bekenstein's proposal. (C) 2018 Elsevier Inc. All rights reserved.
Keywords: Quasinormal modes; Cloud of strings black holes; Greybody factors; Classical fields